2001
DOI: 10.1002/jez.1121
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of duplicated zebrafish cyp19 genes

Abstract: The zebrafish has recently been developed as a good genetic model system. We report here the use of zebrafish to study the regulation of estrogen biosynthesis. The CYP19 gene encodes cytochrome P450 aromatase, which catalyzes the synthesis of estrogens. Two cyp19 genes, termed cyp19a and cyp19b, have been isolated from zebrafish. Sequence comparison shows that Cyp19a and Cyp19b belong to two separate Cyp19 subfamilies. The cyp19a gene is expressed in the ovary, whereas cyp19b is expressed in the brain. The cyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 16 publications
2
42
0
1
Order By: Relevance
“…Besides En1, differences in the expression pattern of Msx zebrafish paralogs and homologous genes of other vertebrates also suggest subfunctionalization of the zebrafish genes after duplication (Ekker et al, 1997). Similar conclusions can be drawn for hedgehog genes (Laforest et al, 1998), Bmp2 (Martinez-Barbera et al, 1997, the transcription factors mitfa and mitfb (Mellgren and Johnson, 2002;Altschmied et al, 2002), cyp19 (Chiang et al, 2001), GlyRalpha genes (Imboden et al, 2001), Notch and Pax6 (Lynch and Force, 2000a). Models such as the DDC model may explain the retention and functional divergence of duplicated genes.…”
Section: The Evolutionary Consequences Of An Ancient Fish-specific Gementioning
confidence: 67%
“…Besides En1, differences in the expression pattern of Msx zebrafish paralogs and homologous genes of other vertebrates also suggest subfunctionalization of the zebrafish genes after duplication (Ekker et al, 1997). Similar conclusions can be drawn for hedgehog genes (Laforest et al, 1998), Bmp2 (Martinez-Barbera et al, 1997, the transcription factors mitfa and mitfb (Mellgren and Johnson, 2002;Altschmied et al, 2002), cyp19 (Chiang et al, 2001), GlyRalpha genes (Imboden et al, 2001), Notch and Pax6 (Lynch and Force, 2000a). Models such as the DDC model may explain the retention and functional divergence of duplicated genes.…”
Section: The Evolutionary Consequences Of An Ancient Fish-specific Gementioning
confidence: 67%
“…Most teleosts have at least two CYP19 genes (P450arom), which encode structurally and functionally distinct P450arom isozymes in ovary ( CYP19a /P450aromA) and brain ( CYP19b/ P450aromB) (Callard and Tchoudakova, 1997;Chiang et al ., 2001;Gelinas et al ., 1998;Kwon et al ., 2001). In this study, we isolated two forms of the aromatase cDNA from the goby, T. okinawae .…”
Section: Discussionmentioning
confidence: 99%
“…We confirmed that both isoforms have aromatization ability as is the case with goldfish (Tchoudakova et al ., 1998) and zebrafish (Chiang et al ., 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The brain of adult fish is well knownfor its high aromatase activity (Pasmanik and Callard, 1985;Pasmanik et al, 1988) corresponding to the strong expression of the cyp19a1b gene, that encodes CYP19A1B (or aromatase B), the brain form of aromatase in fish (Chiang et al, 2001;Tchoudakova et al, 2001). Although the functional significance for this unique feature of the fish brain is not fully understood, the mechanisms underlying this high expression are starting to be well deciphered.…”
Section: Introductionmentioning
confidence: 99%